Estimating the young evolutionary age of marbled crayfish from museum samples - Vogt, Günter (Journal of natural history, 2019)
The obligately parthenogenetic, all-female marbled crayfish, Procambarus virginalis, is a triploid descendant of the similarly looking, sexually reproducing slough crayfish, Procambarus fallax, native to Florida and southern Georgia. We have earlier hypothesised that marbled crayfish may have originated from P. fallax only some 25 years ago, perhaps in captivity. In order to investigate the young evolutionary age hypothesis in more detail, I searched the P. fallax collection of the Smithsonian Institution Museum of Natural History (USNM, Washington, D.C.) for evidence of marbled crayfish before its detection in the German aquarium trade in 1995. In particular, I analysed the sex ratio of P. fallax and the frequency of pure female samples throughout its entire distribution range to detect potentially misidentified marbled crayfish among the P. fallax. If marbled crayfish had originated from P. fallax long ago, spread throughout Florida and Georgia and erroneously been sampled as P. fallax, then the sex ratio of the P. fallax in the collection should be significantly biased towards females and pure female samples should be much more frequent than in related Procambarus species. Comparison of P. fallax (n = 2299) with its closest relatives P. seminolae (n = 801) and P. leonensis (n = 150) revealed female proportions of 55.33%, 53.93% and 54.67%, respectively, which are not significantly different from each other. The average female proportion of the 14 Procambarus species investigated (8641 specimens) was 52.54 +/- 7.54% (mean +/- standard deviation). Moreover, pure female samples consisting of more than 3 specimens that could represent hidden marbled crayfish were not conspicuously more common in P. fallax (2.33%) than in all Procambarus species investigated (1.24 +/- 1.79%). These data suggest that the P. fallax collection of the USNM consists of real, sexually reproducing P. fallax and does most likely not include hidden marbled crayfish, supporting the young evolutionary age hypothesis for marbled crayfish.